2020
DOI: 10.1186/s40644-020-00334-x
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted Imaging (DWI) derived from PET/MRI for lymph node assessment in patients with Head and Neck Squamous Cell Carcinoma (HNSCC)

Abstract: Background To determine the usefulness of Diffusion Weighted Imaging (DWI) derived from PET/MRI in discriminating normal from metastatic lymph nodes and the correlation between the metastatic lymph nodes with the grade and the localization of the primary tumor. Methods Retrospective study of 90 lymph nodes from 90 subjects; 65 patients who had proven histopathological metastatic lymph nodes from (HNSCC) who had undergone 18 F- PET/MRI for clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 50 publications
(57 reference statements)
2
15
0
Order By: Relevance
“…The work strategy and procedure have been published elsewhere [11,12,21]. In brief, the examinations were conducted in a dedicated PET/MRI (3 T) equipment (Biograph mMR, Siemens AG, Erlangen, Germany).…”
Section: Pet/mri Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…The work strategy and procedure have been published elsewhere [11,12,21]. In brief, the examinations were conducted in a dedicated PET/MRI (3 T) equipment (Biograph mMR, Siemens AG, Erlangen, Germany).…”
Section: Pet/mri Imagingmentioning
confidence: 99%
“…PET/MRI parameters were also included (ADC, SUV, TLG, and MTV). MRI sequences were T2-weighted TSE turbo inversion recovery magnitude (TIRM) (TR/TE/TI 3300/37/220 ms, FOV: 240 mm, slice thickness: 3 mm, 224 × 320) coronal plan, T1-weighted turbo spin-echo (TSE) (TR/TE 800/12 ms, FOV: 200 mm, slice thickness: 4 mm, 224 × 320), and T1-weighted TSE Dixon fat suppression (FS) (TR/TE 6500/85 ms, FOV: 200 mm, slice thickness: 4 mm, 256 × 320) transversal and were acquired without an intravenous contrast agent [11,12,21].…”
Section: Pet/mri Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, comparing CT/MRI vs. PET-CT scans, it was demonstrated that FDG-PET-CT is superior to CT/MRI imaging to detect occult neck metastases [ 9 ]. Heusch et al further illustrated that FDG-PET MRI scan combined with diffusion-weighted imaging (DWI) is not superior to ultrasound and FDG-PET-CT scans in the detection of cervical lymph node metastases [ 42 , 43 ]. In this survey, the most frequently used imaging technique for staging the head and neck in OSCC was CT, followed by ultrasound and MRI scans.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond its original neuro-imaging applications, DW has been clinically exploited in oncologic and body imaging thanks to its simplicity, radiation-free nature, needless contrast administration, and convenience as well as outstanding sensitivity and specificity [6] , [20] , [21] . It has been clinically validated for screening of infiltrative primary and secondary osseous lesion as well as for assessing the response to chemotherapy using the whole body–diffusion weighted MR imaging (WB-DW MRI) [22] , [23] .…”
Section: Discussionmentioning
confidence: 99%